Optimization of Gravity Concrete Dams Using the Grasshopper Algorithm (Case Study: Koyna Dam) - Seifollahi, Mehran; Abbasi, Salim; Abraham, John; Norouzi, Reza; Daneshfaraz, Rasoul; Lotfollahi-Yaghin, Mohammad-Ali; Alkan, Ahmet (Geotechnical and geological engineering, 2022)
The aim of this study is to optimize the geometric dimensions of the Koyna concrete weight dam with and without seismic forces using the grasshopper optimizer algorithm (GOA). In the methodology section of this paper, the geometric parameters of the dam are provided as input data to an objective function minimizing the geometric dimensions and concreting volume of the dam body. The present results show that the best model for optimization with the grasshopper algorithm for situations without the effects of seismic forces has a 13.7% reduction in a concrete volume equivalent to 498 cubic meters. The results of the grasshopper algorithm were compared with the results of the particle swarm optimizer (PSO), Gray wolf optimizer (GWO), and LINGO11 algorithms. A comparison of the optimized volume of concrete shows that with the PSO method, volume reductions were: 378 cubic meters 10.4% with the GWO method, 431 cubic meters 11.86% with the LINGO11 process, 82 cubic meters 2.25% with the GOA method, 498 cubic meters 13.7%. The best optimization results were obtained with the effects of seismic forces with a 10.99% reduction in the volume of concrete equal to ~ 400 cubic meters. The results show the superiority of the optimization method of the grasshopper algorithm over other methods. The amount of concrete used in the Koyna dam is 3633 cubic meters, which in the optimized state with LINGO11 method 3551 cubic meters in GWO method 3255, in PSO method 3202, and in GOA method, 3138 cubic meters, which in general, the volume is optimized, respectively 82, 378, 431, and 495 cubic meters.